Preliminary Study of the Affixes in Tagalog - Lopez, Cecilio (The Archive; Vol 1 (1977): Publication One: Selected Writings of Cecilio Lopez in Philippine Linguistics, 2025)
This article is a list of the affixes used in the Tagalog language for the nomen quantitatis (exact expressions of quantity), the nomen agendi , the nomen substantivum , the nomen qualitatis (as predicate and as subject), and the quasi verb.